2021
DOI: 10.1177/20458940211056014
|View full text |Cite
|
Sign up to set email alerts
|

Sex and survival following pulmonary endarterectomy for chronic thromboembolic pulmonary hypertension: a Scandinavian observational cohort study

Abstract: <b>Background</b> Studies have suggested sex−related survival differences in chronic thromboembolic pulmonary hypertension (CTEPH). Whether long−term prognosis differs between men and women following pulmonary endarterectomy (PEA) for CTEPH remains unclear. We investigated sex−specific survival after PEA for CTEPH. <b>Methods</b> We included all patients who underwent PEA for CTEPH at two Scandinavian centers and obtained baseline characteristics and vital statuses from patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Moreover, the study population was too small to evaluate possible sex differences. 30 We can only speculate about the reasons for which patients declined to participate; whether these patients were too ill to answer or were feeling well and were therefore unwilling to take the time to participate is unknown. Finally, our study results may have been affected by the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study population was too small to evaluate possible sex differences. 30 We can only speculate about the reasons for which patients declined to participate; whether these patients were too ill to answer or were feeling well and were therefore unwilling to take the time to participate is unknown. Finally, our study results may have been affected by the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Women with CTEPH had a more adaptive RV and therefore objective signs of disease was visible later in the disease course, resulting in relatively worse outcomes for women owing to the late diagnosis ( 3 , 35 ). Another study ( 13 ) also showed sex-specific differences in cardiopulmonary function in CTEPH patients.…”
Section: Discussionmentioning
confidence: 99%
“…27 Currently, PTE is indicated in patients with segmental and subsegmental pulmonary artery disease with acceptable mid-and long-term results. 6,8,[12][13][14][17][18][19]21,[23][24][25] On the other hand, the balloon pulmonary angioplasty treatment for chronic PA occlusion is a novel technique for the primary treatment of CTHE and secondary treatment for residual PA thrombosis after PTE. 8,11,21,27 Brain hypoperfusion during hypothermia and CA affect brain metabolism and induce apoptosis and death of nerve cells.…”
Section: Hypothermic Circulatory Arrest With Total Arrest Is Anmentioning
confidence: 99%
“…Although the annual incidence of CTHE varies from 1.9 to 3–5 cases per 100,000 population, many cases with CTEPH remain undiagnosed 27 . Currently, PTE is indicated in patients with segmental and subsegmental pulmonary artery disease with acceptable mid‐ and long‐term results 6,8,12–14,17–19,21,23–25 . On the other hand, the balloon pulmonary angioplasty treatment for chronic PA occlusion is a novel technique for the primary treatment of CTHE and secondary treatment for residual PA thrombosis after PTE 8,11,21,27 …”
mentioning
confidence: 99%
See 1 more Smart Citation